Dogs - Ganeri, Anita (Oxford Heinemann Library, 2003)
This series aims to help children develop an understanding of how to care for pets and the needs of different pets. Each book looks at the needs of common pets at different stages of their life-cycles from babies to old age. This deals with dogs.
Include Colour Illustrations, Glossary and Index
Keywords: Dogs